1997
DOI: 10.1016/s0006-3495(97)78355-3
|View full text |Cite
|
Sign up to set email alerts
|

Introducing phase analysis light scattering for dielectric characterization: measurement of traveling-wave pumping

Abstract: Phase analysis light scattering (PALS) was applied to characterize a high-frequency traveling-wave (TW) micropump. Field strength and frequency characteristics were measured for aqueous solutions up to 40 MHz and conductivities of 16 mS/m. The TW field was generated by an ultramicroelectrode array of intercastellated electrodes, which were driven by square-topped signals. Pumping exhibited one major relaxation peak, which strongly increased for conductivities above 4 mS/m. The conductivity dependence of the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…Note that the effect decreases with increasing conductivity. Electrothermal travelling wave pumping experiments [4,22] show that voltages greater than 10 V are required to achieve noticeable fluid velocities, in agreement with the calculated voltages shown in the figures. The velocity measurements given in [22] show that strong thermal convection is obtained for conductivities greater than 1.6 × 10 −2 S m −1 .…”
Section: Fluid Flowsupporting
confidence: 79%
See 1 more Smart Citation
“…Note that the effect decreases with increasing conductivity. Electrothermal travelling wave pumping experiments [4,22] show that voltages greater than 10 V are required to achieve noticeable fluid velocities, in agreement with the calculated voltages shown in the figures. The velocity measurements given in [22] show that strong thermal convection is obtained for conductivities greater than 1.6 × 10 −2 S m −1 .…”
Section: Fluid Flowsupporting
confidence: 79%
“…Electrothermal travelling wave pumping experiments [4,22] show that voltages greater than 10 V are required to achieve noticeable fluid velocities, in agreement with the calculated voltages shown in the figures. The velocity measurements given in [22] show that strong thermal convection is obtained for conductivities greater than 1.6 × 10 −2 S m −1 . In the same work, it was shown that the velocity increases with conductivity (in the measured range of 4 × 10 −3 to 1.6 × 10 −2 S m −1 ), which is a clear indication of Joule heating.…”
Section: Fluid Flowsupporting
confidence: 79%
“…Gimsa et al [9] measures peak fluid velocity of approximately 10 µm s −1 and 25 µm s −1 for a conductivity of 8 mS m −1 and 16 mS m −1 , respectively, both with a driving voltage of 25 V pk-pk. The gap between successive electrodes was 70 µm.…”
Section: Changing the Temperaturementioning
confidence: 99%
“…Calculating the electric field induced force on the particle and its ensuing motion is relatively simple [3]. However, for DEP electrode arrays in general, the electric field not only produces an induced particle motion but is also responsible for an induced fluid flow in the suspending medium [7][8][9][10]. There are several physical mechanisms whereby the electric field can interact with the fluid, ranging from bulk effects such as convection and electrothermal effects to surface effects such as ac electro-osmosis [10].…”
Section: Introductionmentioning
confidence: 99%
“…Electrothermal fluid flow is due to the action of an electric field on thermally induced gradients of conductivity and permittivity in the fluid (Melcher & Firebaugh 1967;Melcher 1981). The gradients of temperature can be produced by external sources, such as strong illumination (Green et al 2000), or caused by the applied electric field through Joule heating (Müller et al 1993;Gimsa, Eppmann & Prüger 1997;Wang, Sigurdson & Meinhart 2005). Observations and estimates show that electrothermal effects are important in microsystems for frequencies of the order of 1 MHz and voltages of the order of 10 V (Green et al 2001;Castellanos et al 2003).…”
Section: Introductionmentioning
confidence: 99%